Assessment of AlZnMgCu alloy powder modification for crack-free laser powder bed fusion by differential fast scanning calorimetry - Zhuravlev, Evgeny; Milkereit, Benjamin; Yang, Bin; Heiland, Steffen; Vieth, Pascal; Voigt, Markus; Schaper, Mirko; Grundmeier, Guido; Schick, Christoph; Kessler, Olaf (Materials & Design)
Additive manufacturing, e.g. by laser powder bed fusion (LPBF), is very attractive for lightweight constructions, as complex and stress-optimised structures integrating multiple functions can be produced within one process. Unfortunately, high strength AlZnMgCu alloys tend to hot cracking during LPBF and thus have not so far been applicable. In this work the melting and solidification behaviour of AlZnMgCu alloy powder variants with particle surface inoculation was analysed by Differential Fast Scanning Calorimetry. The aim is to establish a method that makes it possible to assess powder modifications in terms of their suitability for LPBF on a laboratory scale requiring only small amounts of powder. Therefore, solidification undercooling is evaluated at cooling rates relevant for LPBF. A method for the temperature correction and normalisation of the DFSC results is proposed. Two ways of powder modification were tested for the powder particles surface inoculation by titanium carbide (TiC) nanoparticles: via wet-chemical deposition and via mechanical mixing. A low undercooling from DFSC correlates with a low number of cracks of LPBF-manufactured cubes. It appears that a reduced undercooling combined with reduced solidification onset scatter indicates the possibility of crack-free LPBF of alloys that otherwise tend to hot cracking.
Keywords: Aluminium alloy 7075; Differential fast scanning calorimetry; Solidification; Undercooling; Additive manufacturing

Mikrostrukturausprägung additiv gefertigter Gitterstrukturen - Sieger, Alexander
Mit Hilfe der additiven Fertigung, insbesondere dem pulverbettbasierten selektiven Laserstrahl-schmelzen (LBM), können hochkomplexe Strukturen endkonturnah hergestellt werden. Die große Designfreiheit ermöglicht, zelluläre Leichtbaustrukturen zu erzeugen, deren mikrostrukturellen und mechanischen Eigenschaften direkt vom generativen Fertigungsverfahren abhängen. Insbesondere im Bereich des Leichtbaus bieten zelluläre Strukturen neue Ansätze zur Verminderung des Energieverbrauchs. Um dieses Potential vollständig ausschöpfen zu können, müssen die Effekte, die zum Versagen der Bauteile mit integrierten Gitterstrukturen führen, quantitativ beschrieben und verstanden werden. Dies ist Voraussetzung für eine sichere Auslegung. Dazu werden im Rahmen der vorliegenden Arbeit die charakteristischen Eigenschaften dieser Strukturen sowie die Einflussgrößen im Aufbauprozess näher beleuchtet. Im Rahmen dieser Dissertation werden numerische und experimentelle Untersuchungen von zwei unterschiedlichen Gitterstrukturtypen aus den Werkstoffen 316L und TiAl6V4 vorgestellt. Beide Werkstoffe werden unter monotoner, einachsiger Belastung getestet. Die parallel dazu durchgeführte digitale Bildkorrelation (DIC) ermöglicht gleichzeitig die detaillierte Analyse der lokalen Dehnungsverteilung während der Verformung. Mikrostrukturelle Eigenschaften und die resultierenden Gittercharakteristika werden mit Hilfe von rasterelektronenmikroskopischen Analysemethoden untersucht. Zudem erfolgt die Entwicklung eines Finite-Elemente- Modells, mit der Anforderung eines möglichst geringen Rechenaufwandes. Ein abschließender Vergleich der realen Dehnungsverteilung mit der FE- Analyse verifiziert das Modell.
Keywords: Additive Fertigung; TiAl6V4; 316L; Gitterstrukturen; L-PBF

Untersuchung der mechanischen Eigenschaften, Hintergründe und weitere Entwicklungen im Kunststoff Freiformen - Moritzer, Elmar; Hecker, Felix (Jahresmagazin Kunststofftechnik)

Konstruktionsrichtlinien in der Produktentwicklung - Lammers, Stefan; Kruse, Anne; Gierse, Jan; Tominski, Johannes; Lindemann, Christian-Friedrich (Mehrzieloptimierte und durchgängig automatisierte Bauteilentwicklung für Additive Fertigungsverfahren im Produktentstehungsprozess)

Low Temperature Laser Sintering on a Standard System: First Attempts and Results with PA12 - Menge, Dennis; Schmid, Hans-Joachim
The laser sintering process has been a well-established AM process for many years. Disadvantages of LS are the low material variety and the thermal damage of the unprocessed material. The low temperature laser sintering attacks at this point and processes powder material at a build chamber temperature lower than the recrystallization temperature. This drastic reduction in temperature results in significantly less thermal damage to the material. This work deals with the low temperature laser sintering of Polyamide 12 (PA12) on a commercial, unmodified laser sintering system to compare it to standard laser sintered PA12 and to create the basis for low temperature laser sintering of high temperature materials on such a system. First results by changing the exposure parameters and by fixing parts on a building platform show a processing of PA12 on an EOS P396 at a build chamber temperature less than 100 °C instead of standard approx. 175 °C.
Keywords: Low Temp LS; Low Temperature Laser Sintering; Polyamid 12

Generating Physically Sound Training Data for Image Recognition of Additively Manufactured Parts - Nickchen, Tobias; Heindorf, Stefan; Engels, Gregor (Proceedings of the IEEE/CVF Winter Conference on Applications of Computer Vision)

Funktionsoptimierte AM-Gestaltung eines E-Rotors - Magerkohl, Sebastian; Zimmer, Detmar; Tasche, Lennart; Schaper, Mirko; Urbanek, Stefan; Ponick, Bernd (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)
Die Additive Fertigung bietet ein hohes Maß an Gestaltungsfreiheit und ermöglicht die wirt-schaftliche Nutzung von konventionell schwer zu verarbeitenden Materialien. Diese Merk-male ermöglichen neuartige Lösungsansätze bei Funktionsbauteilen in fast allen Anwen-dungsbereichen. Dieses Potential kann auch im Elektromaschinenbau genutzt werden. Am Bespiel des Rotors einer permanentmagneterregten Synchronmaschine (PMSM) lassen sich die Herausforderungen und Möglichkeiten exemplarisch beschreiben.

Zukunftstechnologie und moderne Antriebe kombiniert: AM in modularen Antriebssystemen - Zimmer, Detmar; Koers, Thorsten; Bührmann, Tobias (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Online Monitoring des Beschichtungsprozesses im Laser Sintern, Systementwicklung und Einflussanalyse - Klippstein, Sven Helge

Influences of Temperature-Dependent Boundary Conditions on Component Properties in Arburg Plastic Freeforming - Moritzer, Elmar; Hecker, Felix; Elsner, Christian Lennart; Hirsch, André (Proceedings of 36th Annual Meeting of Polymer Processing Society (PPS-36))